O sistema defensivo da ilha de santa catarina no século XVIII: história & patrimônio - Lorena Leite (2020)
The present work seeks to study the fortifications built on the Island of Santa Catarina, currently the city of Florianopolis, during the 18th century, and which formed the so-called Defensive System. Initiated by the first Governor and Captain-General of the Captaincy, Brigadier José da Silva Paes, in 1738, these buildings have relevant historical and cultural characteristics, and remain today as national heritage. Analyzing the formation of the theory of Military Architecture and the Officers with an engineer degree in the Portuguese Army, we tried to understand how this type of professional was trained in Portugal in the post-Restoration period, and how those sent to Santa Catarina were instructed within a certain learning tradition. Understanding its historical role in the occupation of the territory and its preservation as heritage, the fortresses built on the Island of Santa Catarina constitute a notable example of the Portuguese defense model, forming a Defensive System that employed highly refined construction projects and defensive strategies. Therefore, from the analysis of the research object, an attempt is made to reflect on the Portuguese way of fortifying, the role of such constructions in the demarcation of the southern border, and their preservation through register as public heritage.